Review of Sport Canada`s targeted excellence approach. Final report (Goss Gilroy Inc., 2017)
This report presents the results of a review of the Government of Canada`s approach to Targeted Excellence funding for Olympic and Paralympic sports. The review is based on evidence gathered through document and literature review, Sport Canada database review, key informant interviews and surveys of athletes, Paralympic and Olympic NSOs` administrators and coaches, and members of the Canadian sport community. The objectives of the review were to: • Determine the degree to which the approach has achieved - or is it likely to achieve - Sport Canada`s Targeted Excellence outcomes; • Assess the intended and unintended impacts of the Targeted Excellence approach and its implementation; and • Inform and strengthen future approaches that support targeted talent development and excellence.